Case series: unusual presentations of congenital lung malformations - SP, Basavanthappa; V, Srinivasa; Pejaver, Rajath; Kumar, Naveen; Giriyappa, Chandan (International Journal of Contemporary Pediatrics, 2017)
Congenital Lung Malformations (CLM) are a group of rare lung abnormalities affecting the airways, parenchyma, and vasculature. Congenital lung malformations encompass several conditions such as Congenital Cystic Adenomatoid Malformation (CCAM), Congenital Lobar Emphysema (CLE), Diaphragmatic hernia, sequestration of lung. A high index of suspicion is necessary to diagnose CLM in children irrespective of the age. Here we present a series of three cases of congenital lung malformations with unusual presentations.